2019
DOI: 10.3389/fendo.2019.00772
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells, Self-Renewal, and Lineage Commitment in the Endocrine System

Abstract: The endocrine system coordinates a wide array of body functions mainly through secretion of hormones and their actions on target tissues. Over the last decades, a collective effort between developmental biologists, geneticists, and stem cell biologists has generated a wealth of knowledge related to the contribution of stem/progenitor cells to both organogenesis and self-renewal of endocrine organs. This review provides an up-to-date and comprehensive overview of the role of tissue stem cells in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 375 publications
(399 reference statements)
0
14
0
4
Order By: Relevance
“…In order to develop complete active matured lineages of neuroendocrine stress system, both endogenously and exogenously derived stress would differentiate the stem cells as well as progenitor cells [124]. It is observed that stress can modulate the number of stem cells in adrenal glands [125].…”
Section: Gender Specific Response To Stressmentioning
confidence: 99%
“…In order to develop complete active matured lineages of neuroendocrine stress system, both endogenously and exogenously derived stress would differentiate the stem cells as well as progenitor cells [124]. It is observed that stress can modulate the number of stem cells in adrenal glands [125].…”
Section: Gender Specific Response To Stressmentioning
confidence: 99%
“…Stem cells are dynamically regulated by signals originating from their niches, helping to regulate appropriate proliferation and differentiation. External and internal stressors influence the process of cell differentiation of stem and progenitor cells in the HPA axis in order to form the fully functional endocrine stress system [72].…”
Section: The Role Of Stem Cells In Covid-19mentioning
confidence: 99%
“…It is composed of anterior (adenohypophysis) and posterior (neurohypophysis) lobes with distinct embryological origin, morphology and functions; the endocrine center is adenohypophysis whose specialized cell types are identified according to the secreted hormone: corticotroph cells produce adrenocorticotropic hormone (ACTH); gonadotrophs, follicle-stimulating (FSH) and luteinizing (LH) hormones; lactotrophs, prolactin (PRL); somatotrophs, growth hormone (GH), and thyrotrophs, thyroid-stimulating hormone (TSH). Undifferentiated pituitary stem cells (PSCs) exist within anterior pituitary and give rise to the three main progenitor lineages, characterized by the expression of essential transcription factors for lineage commitment and terminal differentiation: (i) PIT1positive PSCs differentiate into GH/PRL/TSH-expressing cells, (ii) TPIT-cells originate the ACTH-secreting subpopulation, while (iii) LH/FSH-secreting cells derive from SF1 lineage (14). Secretory cell types also include somato-lactotrophs which release both GH and PRL, and are considered less differentiated precursors of the mature cells releasing the specific hormone.…”
Section: An Overview Of the Human Pituitary Glandmentioning
confidence: 99%